2021
DOI: 10.3389/fenvs.2021.591512
|View full text |Cite
|
Sign up to set email alerts
|

Unpacking Stakeholder Perceptions of the Benefits and Challenges Associated With Urban Greenspaces in Sub-Saharan Africa

Abstract: Urban greenspaces underpin ecosystem service provision in cities and are therefore indispensable for human well-being. Nevertheless, they are increasingly disappearing from cities in Sub-Saharan Africa. Understanding how the stakeholders influencing urban greenspace management perceive the benefits provided by urban greenspaces and the challenges to its conservation and management is critical for reversing this trend. Using Malawi’s capital city, Lilongwe, as a case study, we conducted 44 semi-structured inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 49 publications
0
23
0
Order By: Relevance
“…Fast urbanisation and climate change accompany complex and changing land-lakeatmosphere interactions, requiring city planners and policy makers to carefully determine the direction of their urban growth strategies and consider the cooling effect provided by greenspace and bluespace. Efforts should be more targeted to ensure that they optimise the health and wellbeing of vulnerable inhabitants by maximising ecosystem services, as well as utilising collaborative approaches involving different groups of stakeholders [128].…”
Section: Discussionmentioning
confidence: 99%
“…Fast urbanisation and climate change accompany complex and changing land-lakeatmosphere interactions, requiring city planners and policy makers to carefully determine the direction of their urban growth strategies and consider the cooling effect provided by greenspace and bluespace. Efforts should be more targeted to ensure that they optimise the health and wellbeing of vulnerable inhabitants by maximising ecosystem services, as well as utilising collaborative approaches involving different groups of stakeholders [128].…”
Section: Discussionmentioning
confidence: 99%
“…Respondents in Romania perceived green features as helpful to the ability of a company to attract customers and enhance work environments (Gavrilidis et al, 2020). Stakeholders in Malawi who were involved in urban green space planning, maintenance, and conservation perceived green spaces as potential places for educational activities where, for example, people could receive training on agroforestry practices or environmental issues (Guenat et al, 2021). These stakeholders also identified economic revenue, employment opportunities, and cultural services associated with green spaces.…”
Section: Educational and Economic Benefits Of Ugssmentioning
confidence: 99%
“…The establishment and expansion of urban green spaces is the responsibility of departments associated with adaptation, so it could be assumed that urban green spaces support this strategy for minimizing the negative effects of climate change; urban planners should take this into consideration when considering options for urban green development. If inappropriate urbanization is seen as a barrier to the development of urban green spaces (Guenat et al, 2021), such planning outcomes can be expected to slow the pace of implementing climate change adaptation and mitigation. Planners of UGSs can incorporate findings from studies which have indicated that these spaces can be defined quite broadly.…”
Section: Adaptation and Ugssmentioning
confidence: 99%
See 2 more Smart Citations